Process Evaluation on Medical Record Reporting and Information Usage Iskandar Muda Hospital Nagan Raya Regency - Oka Sahrana; Safrizal Safrizal; Arfah Husna; Dian Fera (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
Medical records are all records and documents about the patient's identities, examinations, treatments, actions and other services provided to the patient. Reporting medical records at Iskandar Muda hospital still does not follow standards. This is due to the lack of discipline of officers in filling out medical records, lack of medical records of officers and related health workers, then also influenced by the Hospital Management Information System that does not yet exist. The purpose of the study was to evaluate the reporting of medical records at Sultan Iskandar Muda hospital. This study uses qualitative research. The results showed that Sultan Iskandar Muda Hospital has been processing medical record data. The procedure of making a report that is not appropriate is the completion of resumes and daily census pain hospitalization. While the proper methods are a recapitulation of outpatient visits, making reports of hospital activities and making morbidity reports of inpatients and outpatients. The medical records unit has produced internal and external reports following the guidelines, and middle-level hospital management has fully used medical record information. It can be concluded that in processing medical record data, there are some obstacles. The procedure of making a report is not following the guidelines, and medical record information has been fully utilized.